The incidence of mild cognitive impairment: A systematic review and data synthesis. Issue 1 (8th March 2019) - Gillis, Cai; Mirzaei, Fariba; Potashman, Michele; Ikram, M. Arfan; Maserejian, Nancy
Abstract: Introduction: Incidence estimates of mild cognitive impairment (MCI) range widely. We obtained contemporary age‐specific MCI incidence rates and examined sources of heterogeneity. Methods: We conducted a systematic review of population‐based studies from the Americas, Europe, and Australia using restrictive inclusion criteria to limit heterogeneity. Incidence was examined using 5‐year age categories for MCI and amnestic/nonamnestic subtypes. Data were synthesized using quantitative and qualitative descriptive analyses and quantitative meta‐analyses. Results: Meta‐analysis estimates (95% CI) of MCI incidence per 1000 person‐years were 22.5 (5.1–51.4) for ages 75–79y, 40.9 (7.7–97.5) for ages 80–84y, and 60.1 (6.7–159.0) for ages 85+y. Despite restrictive inclusion criteria, considerable heterogeneity (measured by I 2 ) remained. Meta‐analysis findings and simple descriptive statistics were consistent and supported by qualitative review. Discussion: Heterogeneity in MCI incidence estimates persisted across age‐specific estimates from population samples, likely reflecting differences in populations and methods. Incidence rate ranges are important to consider with summary point estimates. Highlights: Summary estimates for MCI incidence are not available, largely due to heterogeneity. This study generated summary estimates using a multipronged approach. Heterogeneity in our synthesized data remained, reflecting real‐world challenges. Incidence rate ranges may be more useful guides than single summary point estimates.